Moraes, Roque e Galiazzi, Maria do Carmo. Análise textual discursiva. Herói: Unijuí, 2007. 224 p. - Pereira, Luciana Mendes; Nakayama, Juliana Kiyosen (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; v. 30 n. 59 (2014): jul./dez., 2018)
Resenha